PARALINGUISTIC REPRESENTATION AND FORMATION OF RELIGIOUS CONCEPTS IN ENGLISH AND UZBEK LANGUAGES: A LINGUOCOGNITIVE ANALYSIS - Ikromova Durdonaxon (TADQIQOTLAR, 2026)
Abstract:  This  article  explores  the  role  of  paralinguistic  features  in  the formation and representation of religious concepts in English and Uzbek languages from  a  linguocognitive  perspective.  Paralinguistics,  including  intonation,  pitch, rhythm,  pauses,  and  voice  quality,  plays  a  significant  role  in  conveying  implicit meanings and emotional attitudes in religious discourse. The study examines how these non-verbal elements contribute to the conceptualization of religious ideas and values within  different  linguistic  and  cultural  contexts.  By  comparing  English  and  Uzbek religious communication, the research identifies similarities and differences in the use of  paralinguistic  means  and  their  influence  on  cognitive  perception.  The  findings demonstrate that paralinguistic features are essential in shaping religious understanding and enhancing communicative effectiveness.